2005
DOI: 10.1253/circj.69.1212
|View full text |Cite
|
Sign up to set email alerts
|

Are Low Total Serum Antioxidant Status and Elevated Levels of C-Reactive Protein and Monocyte Chemotactic Protein-1 Associated With Cardiac Syndrome X?

Abstract: Background Cardiac syndrome X, also known as microvascular angina, is characterized by exercise-induced chest pain occurring despite a normal coronary angiogram. Several causes and mechanisms have been proposed to explain both the chest pain and ST segment depression. In this study, the association, if any, between cardiac syndrome X and several factors, including blood total antioxidant status, C-reactive protein (CRP), and monocyte chemotactic protein-1 (MCP-1) levels, was investigated. Methods and ResultsTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
1
11
0
2
Order By: Relevance
“…Low level of antioxidants, or inhibition of the antioxidant enzymes, cause oxidative stress and may damage or kill cells 28 . Thus in the present study, the increase in oxidative stress markers such as MDA levels and the decrease in antioxidant markers such as FRAP and GSH and SOD activity correlated with the presence of CSX, supports the reports regarding the role of oxidative stress in the pathogenesis of CSX 22,23,29 . However, the role of oxidative stress in patient with CSX has not been fully elucidated and we could not find many data in literature about the oxidative stress statusparticularly stated parameters-in CSX patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Low level of antioxidants, or inhibition of the antioxidant enzymes, cause oxidative stress and may damage or kill cells 28 . Thus in the present study, the increase in oxidative stress markers such as MDA levels and the decrease in antioxidant markers such as FRAP and GSH and SOD activity correlated with the presence of CSX, supports the reports regarding the role of oxidative stress in the pathogenesis of CSX 22,23,29 . However, the role of oxidative stress in patient with CSX has not been fully elucidated and we could not find many data in literature about the oxidative stress statusparticularly stated parameters-in CSX patients.…”
Section: Discussionsupporting
confidence: 91%
“…Oxidative stress is thought to be linked to certain cardiovascular diseases. In the literature, there are only two studies revealing the association between CSX and oxidative stress that have shown decreased total antioxidant levels in CSX patients 22,23 . In this study, lipid peroxidation was evaluated by measuring of MDA, which results from free radical damage to the membrane components of the cells and can also deactivate membrane transporters, by forming intra-and inter-molecular crosslinks 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are two studies revealing the relationship between CSX and oxidative stress. Both of them indicated total antioxidant status levels reduced in CSX cases [19,20]. For the first time in the literature, we have shown increased activity of MPO, levels of MDA, and decreased activity of SOD, and levels of NOx in cases with CSX.…”
Section: Before Aftermentioning
confidence: 59%
“…It has been suggested that chronic inflammation is of central importance in atherosclerosis, 31,32 and it has been shown that regular and chronic exercise can suppress overt and subclinical inflammation, 3,34,35 based on the fact that atherosclerosis can be considered as a generalized manifestation of an inflammatory disease. 21 Therefore, we and other investigators have already reported that experimental atherosclerosis in apoE-deficient mice is markedly suppressed by administration of the Fc portion of immunoglobulin, possibly by an antiinflammatory action via the inhibitory Fc receptor IIB.…”
Section: Study Limitationsmentioning
confidence: 99%